CHRONOLOGY AND PETROLOGY OF SILICATES FROM IIE IRON METEORITES: EVIDENCE OF A COMPLEX PARENT BODY EVOLUTION - Bogard D.D.; Garrison D.H.; McCoy T.J. (My University, 2000)
IIE iron meteorites contain silicate inclusions the characteristics of which suggest a parent body similar to that of H-chondrites. However, these silicates show a wide range of alteration, ranging from Netschaevo and Techado, the inclusions of which are little altered, to highly differentiated silicates like those in Kodaikanal, Weekeroo Station, and Colomera, which have lost metal and sulfur and are enriched in feldspar. We find these inclusions to show varying degrees of shock alteration. We made 39Ar-40Ar age determinations of Watson, Techado, Miles, Colomera, and Sombrerete. Watson has an Ar-Ar age of 3.677 +/- 0.007 Gyr, similar to previously reported ages for Kodaikanal and Netschaevo. We suggest that the various determined radiometric ages of these three meteorites were probably reset by a common impact event. The space exposure ages for these three meteorites are also similar to each other and are considerably younger than exposure ages of other IIEs. 39Ar-40Ar ages inferred for the other four meteorites analyzed are considerably older than Watson and are: Techado = 4.49 +/- 0.01 Gyr, Miles = 4.405 +/- 0.012 Gyr, Colomera = 4.470 +/- 0.010 Gyr, and Sombrerete = 4.541 +/- 0.0012 Gyr. These ages are in fair agreement with previously reported Rb-Sr isochron ages for Colomera and Weekeroo Station. Although several mechanisms to form IIE meteorites have been suggested, it is not obvious that a single mechanism could produce a suite of meteorites with very different degrees of silicate differentiation and with isotopic ages that differ by >0.8 Gyr. We suggest that those IIEs with older isotopic ages are a product of partial melting and differentiation within the parent body, followed by mixing of silicate and metal while both were relatively hot. Netschaevo and Watson may have formed by this same process or by impact mixing ~4.5 Gyr ago, but their isotopic ages may have been subsequently reset by shock heating. Kodaikanal apparently is required to have formed more recently, in which case impact melting and differentiation seems the only viable process. We see no compelling reasons to believe that IIE silicate and metal derived from different parent bodies or that the parent body of IIEs was the same as that of H-chondrites.